2012
DOI: 10.1186/1746-4811-8-40
|View full text |Cite
|
Sign up to set email alerts
|

A novel xylogenic suspension culture model for exploring lignification in Phyllostachys bamboo

Abstract: BackgroundSome prominent cultured plant cell lines, such as the BY-2 cell line of tobacco (Nicotiana tabacum cv. ‘Bright Yellow 2’) and the T87 cell line of Arabidopsis (Arabidopsis thaliana L. Heynh., ecotype Columbia) are used as model plant cells. These suspension cell culture systems are highly applicable for investigating various aspects of plant cell biology. However, no such prominent cultured cell lines exist in bamboo species.ResultsWe standardized a novel xylogenic suspension culture model in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
5
29
1
4
Order By: Relevance
“…The TEs that developed in calli were formed within cell clusters. Ogita et al (2012) established a xylogenic suspension culture system using a Phyllostachys species of bamboo, and identified that the most common inter-unit linkages in the bamboo cultured cell lignin were β-aryl ether, phenylcoumaran and resinol structures.…”
Section: In Vitro Tracheary Element Systems With Angiosperm Treesmentioning
confidence: 99%
“…The TEs that developed in calli were formed within cell clusters. Ogita et al (2012) established a xylogenic suspension culture system using a Phyllostachys species of bamboo, and identified that the most common inter-unit linkages in the bamboo cultured cell lignin were β-aryl ether, phenylcoumaran and resinol structures.…”
Section: In Vitro Tracheary Element Systems With Angiosperm Treesmentioning
confidence: 99%
“…Muitos trabalhos de indução de elementos traqueais utilizam diferentes combinações e concentrações de hormônios vegetais (Yamamoto et al, 1997;Ogita et al, 2012;Shen et al, 2013;Yoshimoto et al, 2016). No entanto, alguns compostos sintéticos foram recentemente identificados como indutores da formação de xilema na planta-modelo Arabidopsis thaliana, e validados em outras espécies eudicotiledôneas.…”
Section: Testes De Indução De Transdiferenciação De Elementos Traqueaunclassified
“…Além da auxina, a citocinina também é requerida, visto que a ação de apenas um dos hormônios não resulta na formação de elementos traqueais (Milioni et al, 2001). Assim, diversos estudos tem demonstrado que hormônios vegetais são fatores importantes na regulação da transdiferenciação de elementos traqueais, em espécies vegetais distintas (Fukuda, 1997;Yamamoto et al, 1997;Ogita et al, 2012). O papel da auxina na diferenciação vascular durante o desenvolvimento normal da planta já foi muito bem documentada (Turner et al, 2007).…”
Section: Conclusão Geralunclassified
See 2 more Smart Citations